Roguelike Games - György Norbert Szabados; Éva Bácsné Bába; Veronika Fenyves; Zoltán Bács; Anikó Molnár; Gergely Ráthonyi; Hussain Rizwan; Szabolcs Gergely Orbán (International Journal of Engineering and Management Sciences, 2023)
The spread of the gameable personal computers and game consoles resulted in the diversification of the video game genre, and from the 7th generation of the gaming consoles, the experience support of the games became largely enhanced. These games are now consumable owing to their resolution, the content, the plots are so fascinating so that they tie the gamer to the seat. Gamers seek experiences in the games. Still, such a special genre called roguelike was established, which is characterized by the constant termination of this world of experience in such a way that the gamer, as a results of the high level of difficulty, is obliged to start the game again and again. These new genre games are now leading titles of the new generation consoles, such as Demon’s Souls or the Returnal, gaining huge role in the introduction and sale of the new gaming console PS5. This study aims to reveal specifications of this genre, moreover, aims to describe through empirical research how gamers relate to it, and whether features of these games contribute to the devotion to them or lead to the disappointment from this world of experience.